Strategi pembelajaran sejarah berbasis clarification and disclosure techniques /CDT - Cici Setyowati (Universitas Negeri Malang, 2023)
In the educational process, so that the learning process or student learning can achieve its goals, an appropriate strategy is needed in implementing the learning program. Learning strategies have many forms, but in history subjects the strategies used must be goal oriented from history subjects and have characteristics that are unique to history subjects. Theoretically, strategies that are considered to be able to assist in the process of learning history in achieving its goals, through the method of literature review, one of which is by using a learning strategy based on Clarification and Disclosure Techniques/CDT. The development of this strategy is oriented towards four things: 1) the objectives of the history curriculum itself, 2) learning theory, 3) developing learning strategies, and 4) developing pre-existing learning models. The Clarification and Disclosure Techniques/CDT learning strategy has five stages in its steps, namely 1) orientation, 2) stimulus, 3) exploration and performance, 4) clarification and disclosure, 5) inference and reflection. As a learning strategy, Clarification and Disclosure Techniques/CDT also has many advantages and disadvantages theoretically, so that as a practitioner, in order to know the accuracy of the Clarification and Disclosure Techniques/CDT learning strategy in learning history, there are efforts to take direct action and real action for teachers. teachers in schools to directly practice these learning strategies.Pada proses pendidikan, agar proses pembelajaran atau belajar peserta didik dapat mencapai tujuannya, maka dibutuhkan strategi yang tepat dalam pelaksanaan program pembelajaran. Strategi pembelajaran memiliki banyak macam bentuk, namun dalam mata pelajaran sejarah strategi yang digunakan harus berorientasi pada tujuan dari mata pelajaran sejarah dan memiliki ciri ke khasan terhadap mata pelajaran sejarah. Secara teoritis strategi yang dianggap dapat membantu dalam proses pembelajaran sejarah dalam mencapai tujuannya, dengan melalui metode kajian pustaka, salah satunya adalah dengan menggunakan strategi pembelajaran berbasis Clarification and Disclosure Techniques/CDT. Pengembangan strategi ini berorientasi pada empat hal yaitu 1) tujuan dari kurikulum sejarah sendiri, 2) teori belajar, 3) pengembangan strategi pembelajaran, dan 4) pengembangan model pembelajaran yang telah ada sebelumnya. Strategi pembelajaran Clarification and Disclosure Techniques/CDT memiliki lima tahapan dalam langkah-langkahnya yaitu 1) orientasi, 2) stimulus, 3) eksplorasi dan unjuk kerja, 4) klarifikasi dan pengungkapan, 5) penyimpulan dan refleksi. Sebagai strategi pembelajaran Clarification and Disclosure Techniques/CDT juga memiliki banyak kelebihan dan kelemahan secara teoritis, sehingga secara praktisi agar dapat mengetahui ketepatan dari strategi pembelajaran Clarification and Disclosure Techniques/CDT dalam pembelajaran sejarah, maka ada upaya tindakan secara langsung dan tindakan nyata bagi guru-guru di sekolah untuk mempraktikan secara langsung strategi pembelajaran tersebut.